ENHANCING MULTI-BIT COPLANAR ADDER AND SUBTRACTOR RELIABILITY IN QUANTUM-DOT CELLULAR AUTOMATA - Farhad Ahmed Khan, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Quantum-Dot Cellular Automata (QDCA) represents a promising paradigm for digital circuit design, offering the potential for high-density and low-power computation at the molecular scale. This paper explores the enhancement of reliability in multi-bit coplanar adder and subtractor circuits within the QDCA framework. We begin by introducing the fundamental principles of QDCA and the specific design considerations for multi-bit arithmetic operations. The paper identifies key reliability challenges, including noise sensitivity, variability in quantum dot properties, and precision in electrostatic management. To address these issues, we propose several enhancement techniques, such as advanced error detection and correction methods, redundancy, robust electrostatic management, and adaptive circuit designs. We validate these techniques through extensive experimental testing, evaluating performance metrics such as error rates, circuit speed, and robustness under stress conditions. The results demonstrate significant improvements in circuit reliability and performance, confirming the effectiveness of the proposed methods. The paper concludes with a discussion on the implications of these findings and outlines directions for future research, including advancements in error correction, manufacturing processes, and circuit design. This work contributes to advancing QDCA technology towards practical and scalable digital computing applications.